2017
DOI: 10.1038/labinvest.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma subtypes demonstrate distinct PD-L1 expression profiles

Abstract: PD-L1 expression in the tumor immune microenvironment is recognized as both a prognostic and predictive biomarker in patients with cutaneous melanoma, a finding closely related to its adaptive (IFN-γ-mediated) mechanism of expression. Approximately 35% of cutaneous melanomas express PD-L1, however, the expression patterns, levels, and prevalence in rarer melanoma subtypes are not well described. We performed immunohistochemistry for PD-L1 and CD8 on 200 formalin-fixed paraffin-embedded specimens from patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 58 publications
3
114
0
Order By: Relevance
“…However, our retrospective single‐institution study showed that the current patients who could afford immune checkpoint inhibitors had significantly improved OS when compared with the patients who were treated before immune checkpoint inhibitors became available. Surprisingly, this improvement was seen not only in patients with SSM, but also in those with ALM, the clinical type that is considered to respond poorly to immune checkpoint inhibitors . Therefore, immune checkpoint inhibitors may also improve the prognosis of Asian melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our retrospective single‐institution study showed that the current patients who could afford immune checkpoint inhibitors had significantly improved OS when compared with the patients who were treated before immune checkpoint inhibitors became available. Surprisingly, this improvement was seen not only in patients with SSM, but also in those with ALM, the clinical type that is considered to respond poorly to immune checkpoint inhibitors . Therefore, immune checkpoint inhibitors may also improve the prognosis of Asian melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, these previous studies comprised mainly white populations, in which SSM and LMM are the major clinical types of melanoma . In contrast, Asians manifest a distinct clinicopathological type of melanoma from that of whites and show much higher frequencies of ALM and MUC, which have been shown to be less susceptible to immune checkpoint inhibitors . Although αPD‐1mAb and ipilimumab have demonstrated their efficacy in single‐arm studies, no comparative studies have been published showing improvement of OS by immune checkpoint inhibitors in Asian melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive pattern of PD-L1 expression also predominates in melanoma subtypes, such as ocular, desmoplastic, acral, and mucosal melanomas. 70 Adaptive PD-L1 expression is a positive prognostic feature when expressed by either tumor cells or tumor-associated immune cells. 7 Both melanocyte and immune cell PD-L1 display is primarily IFN- γ driven, though other cytokines such as interleukin10 may preferentially contribute to macrophage as opposed to tumor cell PD-L1 expression.…”
Section: Melanoma and Other Cutaneous Malignanciesmentioning
confidence: 99%
“…The prevalence of PD-L1 expression in melanoma ranges from 24% to 49%,51–53 being highest (~60%) in tumours arising from chronic sun-damaged skin and lowest in uveal melanoma (10%) 54. PD-L1 independently predicts for poorer prognosis, being strongly correlated to tumour thickness, lymphatic and visceral spread, and in BRAF-mutant melanoma, PD-L1 overexpression is an adaptive feature of resistance to BRAF inhibitors 55 56.…”
Section: Pd-l1 Expression In Malignancymentioning
confidence: 99%